THE INFORMATION CONTENT OF METASOMATIC ZIRCONS BY SOME PHYSICAL, MORPHOLOGICAL AND GEOCHEMICAL PROPERTIES - Lazareva, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Typomorfic properties of zircons are widely applied to identify the formation type of intrusive complexes, metamorphic and metasomatic formations, petrofundal reconstructions of material sources of sedimentary basins. There are two possible ways of implementation of the above mentioned possibilities: application of evolutional crystalomorphic analysis method and use of geochemical indicator properties. But information content of the received evaluations probably differs. The purpose of the work was to find out the level of reliability of geochemical, morphological and some physical properties which are easily identified visually and are often applied during mass routine research, in the example of a large block of trace elements data, morphology, colour and transparency of zircon grains extracted from various metasomatites of Suschano-Perzhansk zone (SPZ) and granites of Korosten Pluton (KP) (Ukrainian shield), which is spatially and genetically connected with them. The following tasks have been solved: (1) geochemical typing of zircons; (2) morphological typing of zircons; (3) colour and transparency typing of zircons; (4) trace elements composition of zircons modeling in order to confirm results of previous typing; (5) information content level of geochemical, morphologic and physical properties estimation. As a result, geochemical types of zircons which reflect multiphase formation of SPZ metasomatites were received and the type of zircons which belongs to the main phase of metasomatite formation was identified (by the trace elements ratios and age estimations). Results of geochemical typing were confirmed by geochemical modeling of trace elements composition of zircons which is genetically connected with magmatogenic-hydrothermal system of KP. An attempt of the correlation between visually observed properties and geochemical typing didn’t give desirable results. Grain typing primarily by morphology and possibly by colour can be applied at the preparatory stages of metasomatites research as on a statistical level the correlation is observed.